2023
DOI: 10.1038/s41598-022-27238-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between sarcopenia and clinical outcomes in patients with hepatocellular carcinoma: an updated meta-analysis

Abstract: Although numerous studies have reported the association between sarcopenia and the prognosis of hepatocellular carcinoma (HCC) patients, there is lack of a newer and more comprehensive meta-analysis. Herein, a comprehensive literature search was performed on PubMed, Web of Science, the Cochrane Library, and Embase databases to identify relevant studies published up to February 2022. The outcomes were overall survival (OS), recurrence, progression‐free survival, tumor response, severe postoperative complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 86 publications
(276 reference statements)
1
13
0
Order By: Relevance
“…The phenotype for malnutrition in end-stage liver disease is characterized by sarcopenia, a state of reduced skeletal muscle mass, strength and function and its presence portends a worse prognosis for patients with cirrhosis [36 ▪ ] and hepatocellular carcinoma (HCC) [37]. One recent metanalysis of 50 000 patients with HCC suggests that sarcopenia may be a stronger prognostic indicator than tumor stage [37].…”
Section: Introductionmentioning
confidence: 99%
“…The phenotype for malnutrition in end-stage liver disease is characterized by sarcopenia, a state of reduced skeletal muscle mass, strength and function and its presence portends a worse prognosis for patients with cirrhosis [36 ▪ ] and hepatocellular carcinoma (HCC) [37]. One recent metanalysis of 50 000 patients with HCC suggests that sarcopenia may be a stronger prognostic indicator than tumor stage [37].…”
Section: Introductionmentioning
confidence: 99%
“…2 LSMM can also predict lower objective response rate (odds ratio [OR] = 0.37, 95% CI: 0.17-0.81, P = 0.012) and more drug-related adverse events (OR = 2.23, 95% CI: 1.17-4.28, P = 0.015). 3 In addition, adipose tissue (AT), especially visceral adipose tissue (VAT), plays an important role in HCC. For instance, it was reported that preoperative visceral adiposity predicted poor outcomes after hepatectomy in patients with HCC.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, LSMM was associated with all‐cause mortality in patients with HCC (crude hazard ratio [HR] = 2.04, 95% confidence interval [CI]: 1.74–2.38; adjusted HR = 1.95, 95% CI: 1.60–2.37) 2 . LSMM can also predict lower objective response rate (odds ratio [OR] = 0.37, 95% CI: 0.17–0.81, P = 0.012) and more drug‐related adverse events (OR = 2.23, 95% CI: 1.17–4.28, P = 0.015) 3 . In addition, adipose tissue (AT), especially visceral adipose tissue (VAT), plays an important role in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence that abnormal BC phenotypes predict cancer outcomes. In particular, sarcopenia predicts survival and postoperative complications in head and neck, breast, lung and gastrointestinal tract malignancies, 1–5 as well as recurrence 6–9 . Combinations of abnormal BC have further lethality; cancer patients with sarcopenic obesity are at even greater mortality risk 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…In particular, sarcopenia predicts survival and postoperative complications in head and neck, breast, lung and gastrointestinal tract malignancies, [1][2][3][4][5] as well as recurrence. [6][7][8][9] Combinations of abnormal BC have further lethality; cancer patients with sarcopenic obesity are at even greater mortality risk. 10,11 In order for BC to routinely feature in treatment planning, two broad criteria need to be achieved: an effective time-critical treatment for abnormal BC proven to improve outcomes and an accurate and convenient method of measurement.…”
Section: Introductionmentioning
confidence: 99%